Chapter L'Olandese Volante: da Vasco da Gama a Wagner - Collini, Patrizio (Studi e saggi, 2021)
The legend of the Flying Dutchman has undergone between 1500 and 1800 several metamorphoses. A first hint to it is to be found in the fifth canto of the Lusíadas, where Vasco da Gama's enterprise is presented as a faustian one. But only in the romantic era the legend develops all his spectacular and burlesque resources, and especially in Heine's Schnabelewopski and Wagner's Flying Dutchman.